PENGARUH PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL), MANAJEMEN WAKTU, DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN FAKULTAS EKONOMI UNIVERSITAS NEGERI MEDAN STAMBUK 2021 - Diana Ratna Sari Simanungkalit; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of the implementation of Project-Based Learning (PjBL), time management, and learning motivation on the academic achievement of students in the Office Administration Education Study Program, Faculty of Economics, Universitas Negeri Medan, Class of 2021. The population in this study consisted of all Office Administration Education students from the Class of 2021, totaling 89 students. The sampling technique used was total sampling, so the entire population was taken as the research sample. Data were collected through questionnaires and documentation. Instrument validity was tested using the Product Moment formula, while reliability was tested using the Cronbach’s Alpha technique. Data were analyzed using multiple linear regression with hypothesis testing through Partial Test (t-test), Simultaneous Test (F-test), and the Coefficient of Determination (R²). The results of data processing using SPSS version 25 showed that the implementation of Project-Based Learning (PjBL) had a positive and significant effect on students’ academic achievement. Time management also had a positive and significant effect on academic achievement. Likewise, learning motivation had a positive and significant effect on academic achievement. Simultaneously, the implementation of Project-Based Learning (PjBL), time management, and learning motivation significantly influenced academic achievement. The coefficient of determination of 78.4% indicates that the three independent variables jointly contribute to students’ academic achievement, while the remaining 21.6% is influenced by other factors outside this study.